2021
DOI: 10.1016/j.jbc.2021.100397
|View full text |Cite
|
Sign up to set email alerts
|

Development of a colorimetric α-ketoglutarate detection assay for prolyl hydroxylase domain (PHD) proteins

Abstract: Since the discovery of the prolyl hydroxylases domain (PHD) proteins and their canonical hypoxia-inducible factor (HIF) substrate two decades ago, a number of in vitro hydroxylation (IVH) assays for PHD activity have been developed to measure the PHD–HIF interaction. However, most of these assays either require complex proteomics mass spectrometry methods that rely on the specific PHD–HIF interaction or require the handling of radioactive material, as seen in the most commonly used assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…However, it should be noted that for the Fe 2+ /α‐KG‐dependent oxygenase TfdA (2,4‐dichlorophenoxyacetate/α‐KG dioxygenase) it was reported that addition of dithionite remediated the effects of self‐hydroxylation to some extent [70] . Recently, Haigis and co‐workers have established a colorimetric α‐KG detection assay for the prolyl hydroxylases domain protein family [88] . The α‐KG consumption assay, relying on the derivatization of α‐KG with 2,4‐dinitrophenylhydrazine (2,4‐DNPH, Scheme 5) in the presence of concentrated base (Scheme 4), could also find use for the enzymes described in Table 1.…”
Section: Kinetic Investigations Using Different Assay Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that for the Fe 2+ /α‐KG‐dependent oxygenase TfdA (2,4‐dichlorophenoxyacetate/α‐KG dioxygenase) it was reported that addition of dithionite remediated the effects of self‐hydroxylation to some extent [70] . Recently, Haigis and co‐workers have established a colorimetric α‐KG detection assay for the prolyl hydroxylases domain protein family [88] . The α‐KG consumption assay, relying on the derivatization of α‐KG with 2,4‐dinitrophenylhydrazine (2,4‐DNPH, Scheme 5) in the presence of concentrated base (Scheme 4), could also find use for the enzymes described in Table 1.…”
Section: Kinetic Investigations Using Different Assay Methodsmentioning
confidence: 99%
“…[70] Recently, Haigis and co-workers have established a colorimetric α-KG detection assay for the prolyl hydroxylases domain protein family. [88] The α-KG consumption assay, relying on the derivatization of α-KG with 2,4-dinitrophenylhydrazine (2,4-DNPH, Scheme 5) in the presence of concentrated base (Scheme 4), could also find use for the enzymes described in Table 1. Succinate does not form the colored product.…”
Section: Direct Analysis Of Co-substrates and Byproductsmentioning
confidence: 99%
“…The DNPH colorimetry assay was performed following a modified method from previous reports. , 0.5 mM DNPH solution in a mixture of acetonitrile and 2 N HCl (1/1) was freshly prepared. Furfural solutions of 0, 1 (0.01 mM), 5 (0.05 mM), 10 (0.1 mM), 20 (0.2 mM), and 100 ppm (1.0 mM) and formaldehyde at 0, 1 (0.03 mM), 5 (0.17 mM), 10 (0.33 mM), 20 (0.67 mM), and 100 ppm (3.3 mM) were prepared, respectively.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Meanwhile, colorimetric methods for the in situ detection of aldehydes have been developed with many important applications, including for chemical toxin detection, security screening, food inspection, and disease monitoring, serving as alternatives to traditional analytical methods for rapid and inexpensive determination. , Various methods have been reported to enhance the sensitivity and selectivity of aliphatic and aromatic aldehyde detection, such as fluorescent supramolecular polymers, chemiluminescence (CL) detection of aldehydes derivatized with 2,4-dinitrophenylhydrazine (DNPH), MnO 2 nanosheets, and supramolecular complex. Generally, the colorimetric detection of aldehydes is based on a nucleophilic addition to a carbonyl group by, for example, an amine such as aniline, DNPH, or 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole (Purpald), which results in the formation of an imine, which gives a different UV–vis absorption band. However, these methods for the detection of aldehydes are not applicable to furfurals due to the absence of imine in the product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation